AKTIVITAS OTOT EKSTERMITAS ATAS PADA TEKNIK SERANGAN DALAM OLAH RAGA ANGGAR - Krisna Viandara, Dewa Made; Kusumawati, Yuli; Wahyu Jatmiko, Safari; Wahyu Dewangga, Mahendra (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background : Fencing is a combat sport that requires upper limb strength, speed, and coordination, especially during attack techniques. Muscle activity of the infraspinatus, anterior deltoid, and triceps brachii plays a crucial role in producing quick, accurate, and stable movements during offensive actions. Methods : This study used an observational design with a cross-sectional approach. A total of 36 fencing athletes were divided into three age categories: cadet (13–17 years), junior (17–20 years), and senior (>20 years). Muscle activity was measured using electromyography (EMG) on the selected muscles. Data analysis was performed using One Way ANOVA. Results : The results showed significant differences (p < 0.05) in the activity of the three muscles across age groups. The senior group demonstrated the highest muscle activity, followed by junior and cadet groups. Conclusion : There is a significant difference in upper limb muscle activity during fencing attack techniques based on age category. Specific training programs tailored to the athlete's muscle development stage are needed to improve performance and prevent injuries.